Variation in age, annual usage and resale price of cut-to-length machinery in different regions of Europe. Issue 2 (3rd May 2016) - Malinen, Jukka; Laitila, Juha; Väätäinen, Kari; Viitamäki, Kimmo
ABSTRACT: The high price of cut-to-length machines requires careful planning of investment in new or second-hand machines. The investment is influenced by machine usage, and is also affected by maintenance, insurance and repair costs, harvesting conditions, number of machine relocations, and availability of working opportunities and employment. In this study, age, size, annual usage and price of the cut-to-length harvesters and forwarders for sale in Europe was investigated, using sales data from the online marketplace. The average age of harvesters was 7.3 years and the average age of forwarders was 7.5 years. The newest machines were on offer in the Northern countries (6.5 and 6.1 years for harvesters and forwarders, respectively). The oldest harvesters were on offer in Western Europe (8.1 years) and Eastern Europe (8.2 years) and the oldest forwarders in Eastern Europe (9.9 years). The average annual use of both harvesters and forwarders were notably high in the Baltic and Northern countries compared to the Western and Eastern Europe. On average, the annual use was 1759 and 1913 h year −1 for the harvesters and forwarders, respectively. The average resale price of harvesters was more dependent on age than total use. For forwarders, both age and total usage had a similar explanatory value. For newer CTL machines, aged between 1 and 5 years, the bigger size class of the machine corresponded to higher price. Older machines did not exhibit such correspondence, whereas the annual usage showed high correspondence on the resale value of the machine.